Constructing pedagogic identities: versions of the educator in AE and HE - Janice Malcolm; Miriam Zukas (Adult Education Research Conference, 2000)
This paper analyses the relationships between pedagogic identities in HE and AE, suggesting that HE could build its social purpose orientation and reclaim pedagogy by learning from the AE community.